Low shrinkage frost-resistant concrete and preparation method thereof

By using self-ablative superwater absorbent (SAP) particles in concrete, the problem of difficulty in controlling humidity and insufficient anti-freeze performance during the curing process is solved, and the effect of reducing shrinkage and improving freeze resistance is achieved.

CN119118618BActive Publication Date: 2025-03-18GUIZHOU QICHEN BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411622151.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

In the prior art, it is difficult to obtain sufficient humidity control during the curing process, resulting in insufficient shrinkage and frost resistance, which increases the risk of concrete cracking and frost damage.

Method used

Self-ablative superwater absorbent (SAP) particles are used to reduce the shrinkage of concrete by introducing the moisture required for further hydration into the concrete, and form micropores during the freeze-thaw cycle, providing space for water freezing and expansion and improving the anti-freeze performance.

Benefits of technology

It effectively reduces the shrinkage rate of concrete and the mass loss rate after freeze-thaw cycle, and significantly improves the freezing resistance and durability of concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of cement-based building materials, and in particular to a low-shrinkage frost-resistant concrete and a preparation method thereof. The present invention synthesizes a kind of SAP particles with self-ablation characteristics, and adds the SAP particles to concrete, utilizes the characteristics of the SAP particles that autonomously release water and ablate in the concrete, reduces the shrinkage of the concrete, and the micropores formed by the ablation provide more favorable water freezing expansion space for the concrete during the freeze-thaw cycle, thereby greatly improving the anti-freeze performance of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, in particular to a low-shrinkage frost-resistant concrete and a preparation method thereof. Background Art

[0002] During the concrete curing construction process, concrete is often difficult to be fully cured.

[0003] This is because the relative humidity during the concrete curing stage is affected by many factors, such as environmental changes (such as fluctuations in temperature and humidity), limitations of curing equipment (such as insufficient or untimely water supply), and errors in human operations (such as failure to water and cover as required).

[0004] These factors may cause fluctuations in humidity inside and on the surface of the concrete, which in turn affects the curing effect and quality of the concrete and increases the risk of concrete cracking.

[0005] Especially in the case of tight construction schedules and low water-cement ratio concrete, the problems of autogenous shrinkage and drying shrinkage become more prominent, further increasing the risk of concrete cracking.

[0006] The temperature in extremely cold regions is low and the climate alternates between freezing and thawing. In these regions, concrete in hydraulic engineering, ports, roads, bridges and other engineering projects is easily frozen and deteriorated.

[0007] The shrinkage and freezing of concrete structures cause great harm to their safety and durability. Therefore, research on how to reduce the shrinkage of concrete and improve its frost resistance is of great practical significance.

[0008] Reference 1 (YE Guang, VTNGUYEN. Analysis of the mechanism of rice husk ash inhibiting the shrinkage of ultra-high performance concrete (English) [J]. Journal of the Chinese Ceramic Society, 2012, 40(02): 212-216.) published a method for reducing the shrinkage of concrete.

[0009] The technology uses the properties of rice husk ash to reduce the autogenous shrinkage problem of high-performance concrete.

[0010] Rice husk ash contains a high proportion of active SiO2, which can react with cement hydration products to form calcium silicate gel. This gel can fill the voids inside the concrete, increase the density of the material, and thus reduce the shrinkage of the concrete.

[0011] The porous structure is conducive to the storage and release of internal moisture.

[0012] At the same time, the special porous structure of rice husk ash can store and release internal moisture, allowing moisture to circulate inside the concrete, thereby reducing the self-shrinkage of concrete.

[0013] Reference 2 (Han Song, An Mingzhe, Guo Rui, et al. Research on the anti-cracking performance of high-performance concrete cured with expanded clay [J]. Journal of Building Materials, 2015, 18(05): 742-748.) published a method to reduce concrete shrinkage.

[0014] This technology uses expanded clay to replace part of the aggregate in concrete, thereby reducing the shrinkage of concrete.

[0015] Expanded clay has a certain water absorption capacity and releases water within a period of time after concrete pouring, providing the cement with the water needed for further hydration, thereby reducing the shrinkage of concrete.

[0016] Reference 3 (Zhichao Liu, Will Hansen. A geometrical model for void saturation in air-entrained concrete under continuous water exposure [J]. construction and building materials, 2016, 124: 475-484.) published a method to reduce the expansion and deterioration of concrete caused by freeze-thaw cycles.

[0017] This technology uses air-entraining agents to generate a large number of fine bubbles inside the concrete, which help optimize the pore distribution of the concrete.

[0018] These bubbles provide ample room for expansion when the moisture freezes, thereby improving the concrete's ability to resist freeze-thaw cycles and enhancing the overall durability of the material.

[0019] The above-mentioned technologies have the following shortcomings: (1) Document 1 Due to the collapsed structure of rice husk ash particles during the grinding process, extremely fine particles may have an adverse effect on the efficiency of internal curing of concrete.

[0020] (2) Reference 2 The cylindrical particles of clay aggregate have a regular shape and a large specific surface area, which makes it easy to form cracks in concrete and is not suitable for preparing high-strength concrete.

[0021] (3) Reference 2 The lack of small-sized ceramsite sand in ceramsite particles leads to inappropriate aggregate grading, which creates a large number of voids and cracks in the concrete, reducing the performance of the concrete.

[0022] (4) Reference 3 The effect of air-entraining agent is easily affected by temperature and construction process. At the same time, it has a complex interaction relationship with other admixtures, which may weaken the effect of the introduced bubbles and form an unstable pore structure.

[0023] SAP can provide cement with the water needed for further hydration through water release and shrinkage, thereby reducing the shrinkage of concrete. The pores formed by SAP water release and shrinkage are similar to pores, which can provide sufficient expansion space for the water in the concrete when it freezes, thereby improving the anti-freezing performance of the concrete. However, conventional SAP has the risk of re-expansion, which reduces the pore-forming effect of SAP to a certain extent. Summary of the invention

[0024] In order to solve the problems existing in the prior art, the present invention provides a low shrinkage frost-resistant concrete. Specifically, the present invention synthesizes a kind of SAP particles with self-ablation characteristics and adds them to concrete, so as to reduce the shrinkage of concrete by utilizing the self-release of water and ablation in the concrete. The micropores formed by ablation provide more favorable water freezing and expansion space for the concrete during the freeze-thaw cycle, thereby greatly improving the frost resistance of the concrete.

[0025] Specifically, the low shrinkage frost-resistant concrete of the present invention is composed of the following raw materials: cement, admixture, coarse aggregate, fine aggregate, admixture, water, and self-dissolving SAP particles.

[0026] Wherein, the preparation process of the self-ablative SAP particles is:

[0027] ① Prepare 15-45% sodium hydroxide solution and 2.8-4.5% ammonium persulfate solution.

[0028] ② Add sodium hydroxide solution to acrylic acid and stir to prepare sodium acrylate solution, the molar ratio of acrylic acid to sodium hydroxide is 1:0.6-0.75,

[0029] ③ Add acrylamide, N'N-methylenebisacrylamide, and 2-hydroxyethyl acrylate to the sodium acrylate solution, add water and stir under nitrogen protection until fully dissolved. The mass ratio of acrylamide, N'N-methylenebisacrylamide, 2-hydroxyethyl acrylate, and sodium acrylate is (10-20):1:(2-3):(3-5).

[0030] ④ Raise the temperature, stir with a magnetic stirrer and drop ammonium persulfate solution, then add polyvinyl alcohol powder and gelatinized starch. 60 Irradiation in a Co radiation field, the reaction obtains a hydrogel, the mass ratio of acrylamide, polyvinyl alcohol, and gelatinized starch is (2-3):1:(0.1-0.2),

[0031] ⑤ Rinse the hydrogel and place it in anhydrous ethanol to remove impurities.

[0032] ⑥ Vacuum drying, ball milling, and sieving to obtain 10-50 μm self-ablative SAP particles.

[0033] As an important cement-based material additive, SAP particles have a shrinkage reduction mechanism mainly in that they introduce water required for further hydration into concrete, thereby reducing the shrinkage of concrete. The present invention independently develops a self-ablating SAP particle, which first has the water absorption and expansion characteristics of ordinary SAP particles. When the internal humidity of the concrete decreases, it can release water to provide cement with water required for further hydration, thereby achieving the expected effect of controlling shrinkage. The self-ablating SAP particles prepared by the present invention can decompose and melt by themselves in the alkaline environment of cement-based materials to form holes. These holes can provide sufficient space for the volume expansion of water in concrete when it freezes, thereby improving the anti-freeze performance of concrete. Although ordinary SAP particles shrink and produce micropores after releasing water in concrete, they will absorb part of the water during the freeze-thaw cycle. It will not have an impact on the initial freeze-thaw cycle of concrete, but it still cannot avoid the damage caused by the long-term freeze-thaw process of concrete. The present invention uses self-ablating SAP particles to solve this technical problem.

[0034] The self-dissolving SAP particles prepared by the present invention have excellent compatibility with concrete and can be directly added into cement and stirred evenly.

[0035] Preferably, the cement is at least one of Portland cement, ordinary Portland cement, sulphoaluminate cement, aluminate cement and phosphate cement. More preferably, the cement strength grade is greater than or equal to 42.5.

[0036] Preferably, the admixture is at least one of fly ash, mineral powder, steel slag powder, silica ash and rice husk ash.

[0037] Preferably, at least one of the coarse aggregate crushed stone, pebbles and recycled coarse aggregate has a particle size of 5-25 mm and is continuously assembled.

[0038] Preferably, the fine aggregate is at least one of river sand, quartz sand and machine-made sand, and has a fineness modulus of 2.0-2.4.

[0039] Preferably, the admixture is at least one of a water reducer, a thickener, a retarder, an early strength agent, and an accelerator.

[0040] More preferably, the water reducer is a polycarboxylate water reducer.

[0041] Preferably, the water-cement ratio of concrete is 0.25-0.55, and the sand ratio is 0.35-0.42.

[0042] Preferably, the amount of the self-ablative SAP particles is 0.1-0.5% of the mass of the gelling material.

[0043] Preferably, the stirring speed in each step of the preparation process of the self-ablating SAP particles is 200-600 r / min.

[0044] Preferably, step ④ is heated to 75-80°C.

[0045] Preferably, the vacuum drying temperature in step ⑥ is 80-90°C.

[0046] The present invention also relates to a method for preparing the low shrinkage frost-resistant concrete, which specifically comprises the following steps:

[0047] 1) Add self-dissolving SAP particles and cement into the mixer and mix well.

[0048] 2) Add fine aggregate and coarse aggregate and continue to mix evenly.

[0049] 3) Add the admixture into water to prepare the admixture solution, add it into the mixer, stir evenly, shape it, and cure it.

[0050] Preferably, step 3) is performed by standard curing for 28 days.

[0051] The present invention has the following technical effects:

[0052] 1. The raw materials for the production of self-ablative SAP particles are cheap and readily available, and the preparation process is simple.

[0053] 2. Self-dissolving SAP particles have good dispersibility and can be directly mixed with concrete raw materials, which is convenient for the construction process and does not require additional steps or equipment.

[0054] 3. The application of self-melting SAP particles can improve the frost resistance of concrete and reduce shrinkage, thereby improving the durability and service life of concrete. DETAILED DESCRIPTION

[0055] In order to characterize the technical effect of the present invention, concrete was prepared and its fluidity, mechanical properties and durability were tested. In the concrete preparation process, P·O42.5 cement was used, secondary fly ash and S95 grade mineral powder were used as admixtures, 5-25mm aggregate crushed stone was used as coarse aggregate, 2.3 river sand with fineness modulus was used as fineness modulus, polycarboxylate water reducer and hydroxypropyl methyl cellulose ether were used as admixtures, and the concrete mix ratio was 400 parts of cement, 60 parts of fly ash, 40 parts of mineral powder, 1135 parts of crushed stone, 755 parts of river sand, 5.5 parts of water reducer, 1 part of cellulose ether, 155 parts of water, and 2 parts of SAP particles.

[0056] Example 1

[0057] The preparation process of SAP particles is as follows:

[0058] ① Prepare 30% sodium hydroxide solution and 3.5% ammonium persulfate solution.

[0059] ② Add sodium hydroxide solution to acrylic acid and stir to prepare sodium acrylate solution, the molar ratio of acrylic acid to sodium hydroxide is 1:0.65,

[0060] ③ Add acrylamide, N'N-methylenebisacrylamide, and 2-hydroxyethyl acrylate to the sodium acrylate solution, add water and stir under nitrogen protection until fully dissolved. The mass ratio of acrylamide, NN-methylenebisacrylamide, 2-hydroxyethyl acrylate, and sodium acrylate is 13:1:2:5.

[0061] ④ Raise the temperature to 80℃, stir with a magnetic stirrer and drop ammonium persulfate solution, then add polyvinyl alcohol powder and gelatinized starch. 60 Irradiation in Co radiation field, the reaction to obtain hydrogel, acrylamide, polyvinyl alcohol, gelatinized starch mass ratio of 2.3:1:0.2,

[0062] ⑤ Rinse the hydrogel and place it in anhydrous ethanol to remove impurities.

[0063] ⑥ Dry in vacuum at 85°C, ball-mill, and sieve to obtain 10-50 μm self-ablative SAP particles.

[0064] After testing, the concrete fluidity is 690mm, workability is good, 3d shrinkage is 0.01%, 7d shrinkage is 0.013%, 28d shrinkage is 0.015%, 90d shrinkage is 0.015%, mass loss rate after 50 freeze-thaw cycles is 0.2%, mass loss rate after 100 freeze-thaw cycles is 0.5%, and mass loss rate after 300 freeze-thaw cycles is 0.7%.

[0065] Example 2

[0066] The preparation process of SAP particles is as follows:

[0067] ① Prepare 30% sodium hydroxide solution and 3.5% ammonium persulfate solution.

[0068] ② Add sodium hydroxide solution to acrylic acid and stir to prepare sodium acrylate solution, the molar ratio of acrylic acid to sodium hydroxide is 1:0.7,

[0069] ③ Add acrylamide, N'N-methylenebisacrylamide, and 2-hydroxyethyl acrylate to the sodium acrylate solution, add water and stir under nitrogen protection until fully dissolved. The mass ratio of acrylamide, NN-methylenebisacrylamide, 2-hydroxyethyl acrylate, and sodium acrylate is 15:1:3:4.

[0070] ④ Raise the temperature to 80℃, stir with a magnetic stirrer and drop ammonium persulfate solution, then add polyvinyl alcohol powder and gelatinized starch. 60Irradiation in Co radiation field, the reaction to obtain hydrogel, acrylamide, polyvinyl alcohol, gelatinized starch mass ratio of 2.3:1:0.1,

[0071] ⑤ Rinse the hydrogel and place it in anhydrous ethanol to remove impurities.

[0072] ⑥ Dry in vacuum at 80°C, ball-mill, and sieve to obtain 10-50 μm self-ablative SAP particles.

[0073] After testing, the concrete fluidity is 700mm, workability is good, 3d shrinkage is 0.008%, 7d shrinkage is 0.011%, 28d shrinkage is 0.013%, 90d shrinkage is 0.014%, mass loss rate after 50 freeze-thaw cycles is 0.1%, mass loss rate after 100 freeze-thaw cycles is 0.4%, and mass loss rate after 300 freeze-thaw cycles is 0.5%.

[0074] Comparative Example 1

[0075] In Comparative Example 1, polyacrylic acid cross-linked acrylamide type SAP was ball-milled to obtain SAP particles with a particle size of 10-50 μm.

[0076] After testing, the concrete fluidity is 660mm, the workability is good, the 3d shrinkage is 0.014%, the 7d shrinkage is 0.017%, the 28d shrinkage is 0.021%, the 90d shrinkage is 0.022%, the mass loss rate after 50 freeze-thaw cycles is 0.5%, the mass loss rate after 100 freeze-thaw cycles is 0.9%, and the mass loss rate after 300 freeze-thaw cycles is 1.3%.

[0077] Comparative Example 2

[0078] The preparation process of SAP particles is as follows:

[0079] ① Prepare 30% sodium hydroxide solution and 3.5% ammonium persulfate solution.

[0080] ② Add sodium hydroxide solution to acrylic acid and stir to prepare sodium acrylate solution, the molar ratio of acrylic acid to sodium hydroxide is 1:0.65,

[0081] ③ Add N'N-methylenebisacrylamide to the sodium acrylate solution, add water and stir under nitrogen protection until fully dissolved. The mass ratio of N'N-methylenebisacrylamide to sodium acrylate is 1:5.

[0082] ④ Raise the temperature to 80℃, stir with a magnetic stirrer and drop ammonium persulfate solution, then add polyvinyl alcohol powder and gelatinized starch. 60 Irradiation in Co radiation field, the reaction to obtain hydrogel, N'N-methylenebisacrylamide, polyvinyl alcohol, gelatinized starch mass ratio of 2.3:1:0.2,

[0083] ⑤ Rinse the hydrogel and place it in anhydrous ethanol to remove impurities.

[0084] ⑥ Dry in vacuum at 85°C, ball-mill, and sieve to obtain 10-50 μm SAP particles.

[0085] After testing, the concrete fluidity is 650mm, workability is good, 3d shrinkage is 0.015%, 7d shrinkage is 0.017%, 28d shrinkage is 0.02%, 90d shrinkage is 0.023%, mass loss rate after 50 freeze-thaw cycles is 0.4%, mass loss rate after 100 freeze-thaw cycles is 0.8%, and mass loss rate after 300 freeze-thaw cycles is 1.7%.

[0086] Comparative Example 3

[0087] The preparation process of SAP particles is as follows:

[0088] ① Prepare 30% sodium hydroxide solution and 3.5% ammonium persulfate solution.

[0089] ② Add sodium hydroxide solution to acrylic acid and stir to prepare sodium acrylate solution, the molar ratio of acrylic acid to sodium hydroxide is 1:0.65,

[0090] ③ Add acrylamide to the sodium acrylate solution, add water and stir under nitrogen protection until fully dissolved. The mass ratio of acrylamide to sodium acrylate is 13:5.

[0091] ④ Raise the temperature to 80℃, stir with a magnetic stirrer and drop ammonium persulfate solution, then add polyvinyl alcohol powder and gelatinized starch. 60 Irradiation in Co radiation field, the reaction to obtain hydrogel, acrylamide, polyvinyl alcohol, gelatinized starch mass ratio of 2.3:1:0.2,

[0092] ⑤ Rinse the hydrogel and place it in anhydrous ethanol to remove impurities.

[0093] ⑥ Dry in vacuum at 85°C, ball-mill, and sieve to obtain 10-50 μm SAP particles.

[0094] After testing, the concrete fluidity is 670mm, the workability is good, the 3d shrinkage is 0.016%, the 7d shrinkage is 0.021%, the 28d shrinkage is 0.025%, the 90d shrinkage is 0.029%, the mass loss rate after 50 freeze-thaw cycles is 0.7%, the mass loss rate after 100 freeze-thaw cycles is 1.1%, and the mass loss rate after 300 freeze-thaw cycles is 1.9%.

[0095] Comparative Example 4

[0096] The preparation process of SAP particles is as follows:

[0097] ① Prepare 30% sodium hydroxide solution and 3.5% ammonium persulfate solution.

[0098] ② Add sodium hydroxide solution to acrylic acid and stir to prepare sodium acrylate solution, the molar ratio of acrylic acid to sodium hydroxide is 1:0.65,

[0099] ③ Add acrylamide, N'N-methylenebisacrylamide, and 2-hydroxyethyl acrylate to the sodium acrylate solution, add water and stir under nitrogen protection until fully dissolved. The mass ratio of acrylamide, NN-methylenebisacrylamide, 2-hydroxyethyl acrylate, and sodium acrylate is 13:1:2:5.

[0100] ④ Raise the temperature to 80°C, stir with a magnetic stirrer and drop ammonium persulfate solution to react to obtain a hydrogel.

[0101] ⑤ Rinse the hydrogel and place it in anhydrous ethanol to remove impurities.

[0102] ⑥ Dry in vacuum at 85°C, ball-mill, and sieve to obtain 10-50 μm SAP particles.

[0103] After testing, the concrete fluidity is 710mm, the workability is general, the SAP particles partially float up and there is agglomeration phenomenon, the 3d shrinkage rate is 0.018%, the 7d shrinkage rate is 0.022%, the 28d shrinkage rate is 0.027%, the 90d shrinkage rate is 0.029%, the mass loss rate after 50 freeze-thaw cycles is 0.6%, the mass loss rate after 100 freeze-thaw cycles is 1.1%, and the mass loss rate after 300 freeze-thaw cycles is 2.1%.

[0104] Comparison Example

[0105] The concrete mix ratio is 400 parts of cement, 60 parts of fly ash, 40 parts of mineral powder, 1135 parts of crushed stone, 755 parts of river sand, 5.5 parts of water reducer, 1 part of cellulose ether, and 155 parts of water.

[0106] After testing, the concrete fluidity is 700mm, the workability is good, the 3d shrinkage is 0.016%, the 7d shrinkage is 0.02%, the 28d shrinkage is 0.034%, the 90d shrinkage is 0.035%, the mass loss rate after 50 freeze-thaw cycles is 1.7%, the mass loss rate after 100 freeze-thaw cycles is 3.6%, and the mass loss rate after 300 freeze-thaw cycles is 6.8%.

[0107] It can be seen that the use of the self-ablating SAP particles of the present invention can reduce the shrinkage of concrete and improve the frost resistance of concrete, especially the frost resistance of concrete after multiple freeze-thaw cycles is significantly improved.

[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low shrinkage frost-resistant concrete, characterized in that: It is composed of the following raw materials: cement, admixture, coarse aggregate, fine aggregate, admixture, water, self-dissolving SAP particles, The preparation process of the self-ablating SAP particles is as follows: ① Prepare 15-45% sodium hydroxide solution and 2.8-4.5% ammonium persulfate solution. ② Add sodium hydroxide solution to acrylic acid and stir to prepare sodium acrylate solution, the molar ratio of acrylic acid to sodium hydroxide is 1:0.6-0.75, ③ Add acrylamide, N'N-methylenebisacrylamide, and 2-hydroxyethyl acrylate to the sodium acrylate solution, add water and stir under nitrogen protection until fully dissolved. The mass ratio of acrylamide, N'N-methylenebisacrylamide, 2-hydroxyethyl acrylate, and sodium acrylate is (10-20):1:(2-3):(3-5). ④ Raise the temperature, stir with a magnetic stirrer and drop ammonium persulfate solution, then add polyvinyl alcohol powder and gelatinized starch. 60 Irradiation in a Co radiation field, the reaction obtains a hydrogel, the mass ratio of acrylamide, polyvinyl alcohol, and gelatinized starch is (2-3):1:(0.1-0.2), ⑤ Rinse the hydrogel and place it in anhydrous ethanol to remove impurities. ⑥ Vacuum drying, ball milling, and sieving to obtain 10-50 μm self-ablative SAP particles. The admixture is at least one of a water reducing agent, a thickening agent, a retarder, an early strength agent, and an accelerator. The water-cement ratio of concrete is 0.25-0.55, the sand ratio is 0.35-0.42, and the amount of self-dissolving SAP particles is 0.1-0.5% of the mass of the cementitious material.

2. The low shrinkage frost-resistant concrete according to claim 1, characterized in that: The cement is at least one of silicate cement, ordinary silicate cement, sulphoaluminate cement, aluminate cement and phosphate cement.

3. The low shrinkage frost-resistant concrete according to claim 1, characterized in that: The admixture is at least one of fly ash, mineral powder, steel slag powder, silica ash and rice husk ash.

4. The low shrinkage frost-resistant concrete according to claim 1, characterized in that: The coarse aggregate is at least one of crushed stone, pebble and recycled coarse aggregate, and the particle size is 5-25 mm and is continuously assembled.

5. The low shrinkage frost-resistant concrete according to claim 1, characterized in that: The fine aggregate is at least one of river sand, quartz sand and machine-made sand, and has a fineness modulus of 2.0-2.

4.

6. The low shrinkage frost-resistant concrete according to claim 1, characterized in that: The stirring speed is 200-600r / min.

7. The low shrinkage frost-resistant concrete according to claim 1, characterized in that: Step ④ is heated to 75-80°C, and step ⑥ is vacuum dried at 80-90°C.

8. The method for preparing low shrinkage frost-resistant concrete according to any one of claims 1 to 7, characterized in that: The steps include: 1) Add self-dissolving SAP particles and cement into the mixer and mix well. 2) Add fine aggregate and coarse aggregate and continue to mix evenly. 3) Add the admixture into water to prepare the admixture solution, add it into the mixer, stir evenly, shape it, and cure it.

Citation Information

Patent Citations

  • Geopolymer concrete containing temperature-sensitive SAP and preparation method thereof

    CN117886560A